2008
DOI: 10.3174/ajnr.a1222
|View full text |Cite
|
Sign up to set email alerts
|

Cervical CT-Guided, Selective Nerve Root Blocks: Improved Safety by Dorsal Approach: Fig 1.

Abstract: SUMMARY:Cervical transforaminal blocks are frequently performed as a treatment of cervical radicular pain. These blocks are performed mostly under fluoroscopy, but a CT-guided technique also has been described. We describe a modification that leads to a more extraforaminal than transforaminal and equally selective nerve root block. C ervical selective nerve root blocks (CSNRB) are commonly performed with fluoroscopic guidance.1 However, CTguidance is also possible and has been described. CT guidance offers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…They vary in the description of patient position, needle technique, and use of contrast. [3][4][5][6][7] Our study is the largest one to evaluate CT-guided CTSI and the first to explore needle position, to our knowledge. We did not have any reported complications and found that junctional and foraminal zone needle locations provided similar high rates of intraforaminal distribution of contrast, significantly higher than that for the extraforaminal needle position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They vary in the description of patient position, needle technique, and use of contrast. [3][4][5][6][7] Our study is the largest one to evaluate CT-guided CTSI and the first to explore needle position, to our knowledge. We did not have any reported complications and found that junctional and foraminal zone needle locations provided similar high rates of intraforaminal distribution of contrast, significantly higher than that for the extraforaminal needle position.…”
Section: Discussionmentioning
confidence: 99%
“…3 The aim of CTSI is to deliver steroids and/or local anesthetic medication into the perineural epidural compartment of the inflamed nerve root and close to the source of radiculitis, which may be the result of disk herniation or arthropathic stenosis. Authors differ regarding the ideal site of needle-tip placement, [3][4][5][6][7] yet small but critical variations in needle positioning could significantly impact drug delivery and therapeutic efficacy. Cho 4 describes a solely extraforaminal technique that does not use contrast material for CT-guided CTSI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 CT guidance offers the advantage of enhanced anatomic resolution with a more precise needle-tip positioning. 9 It is, however, seen as more time-consuming and likely to involve more radiation exposure. In both fluoroscopic and CT-guided CSNRBs, the aim is to block the root in the foramen.…”
mentioning
confidence: 99%
“…Some assume that a relatively deep position, with the needle tip within the outer neural foramen and immediately adjacent to the targeted nerve root, is required for proper analgesic and steroid efficacy, 3,10,18 while others advocate a more cautious, extraforaminal needle tip position to minimize the risk of complications. 8,19,20 Junctional and foraminal needle tip positions have been previously shown to have higher rates of foram- inal contrast flow compared with the extraforaminal needle position, 10 though contrast dispersal pattern was shown not to correlate with pain relief in 1 study. 21 To our knowledge, we are the first to observe, on CT-guided TFESI, contrast appearing within vessels during steroid/analgesic cocktail injection, a finding we believe depicts intravascular injection of steroid and analgesic.…”
Section: Discussionmentioning
confidence: 85%